S31 Application of modern molecular microbiological techniques to identify treatable chronic bacterial airway infection in severe asthma. (December 2018) - Jabeen, M; Street, T; Foster, D; Hood, D; Sanderson, N; Pavord, I; Klenerman, P; Hinks, TSC
Abstract : Background: Haemophilus influenzae is emerging as the commonest pathogenic microorganism isolated from severe asthmatic airways; it is associated with sputum neutrophilia and may confer steroid resistance. Previous metagenomics studies in asthma were limited by lack of consistent clinical phenotyping and inadequate sequencing depth for species-level bacterial identification. We hypothesise that chronic bacterial infection constitutes a 'treatable trait' in non-eosinophilic severe asthma but its prevalence, clinical phenotype and reliable biomarkers need to be defined. Non-typeable Haemophilus influenzae strains (NTHi) can persist within the epithelium and cause episodic airways infections. Mucosal-associated invariant T (MAIT) cells are innate-like lymphocytes which protect against pulmonary bacterial infection, and respond to NTHi in the presence of professional antigen presenting cells (APCs) via MR1, a molecule expressed ubiquitously in many cell types including epithelial cells. It is not known whether NTHi-infected epithelial cells directly activate MAIT cells. Aims: (1) Identify and characterise the sub-phenotype of severe asthmatics with chronic bacterial airways infection using modern molecular microbiological techniques (2) Determine whether MAIT cells directly respond to intra-epithelial infection with NTHi Methods: Analysis of induced sputum samples from stable well-phenotyped severe asthmatics using culture, MALDI-TOF, RT-qPCR and metagenomic sequencing of total DNA extracts using the MiSeq platform. In vitro co-culture of MAIT cells with NTHi-infected bronchial epithelial cell lines (BEAS2B) or primary human airway epithelial cells. MAIT cell activation measured using intracellular cytokine staining. Results: In a cohort of patients with severe asthma (n=23) H. influenzae was commonly cultured and subsequently identified as the dominant bacterial species by metagenomic sequencing (n=8, Median% Total bacterial reads=87.8%). Clinically significant infection was confirmed using a validated H. influenzae plasmid-based RT-qPCR assay. H. influenzae culture positive patients had sputum neutrophilia and lower FeNO. NTHi induces modest MAIT cell production of IFN-gamma which is partly MR1 dependent. Conclusions: H. influenzae is a clinically-relevant pathogen in severe asthma that can be identified reliably using molecular microbiological methods. Ongoing analysis of a larger patient cohort will allow full characterisation of this clinical phenotype. MAIT cells are able to recognise airway epithelial cells infected with viable intracellular NTHi in the absence of APCs.